Not on the same page: comprehensibility of MBS investment prospectuses - Martin Hibbeln; Ralf Metzler; Werner Osterkamp (Review of Derivatives Research, 2025)
We investigate whether originators of mortgage-backed securities lower the comprehensibility of disclosure documents to obfuscate low security quality. Utilizing commonly used complexity proxies primarily based on the volume of the investment prospectus, we find no impact on the performance of European mortgage-backed securities. In contrast, focusing on the comprehensibility as a combination of prospectus volume and text readability, we find that originators obfuscate low security quality by lowering the comprehensibility of the investment prospectus, resulting in greater defaults and lower returns. Investors only partially price these dimensions of complexity: Since the financial crisis, investors have been demanding a significant risk premium for prospectus volume but not for text readability. These findings underscore the importance of assessing comprehensibility of disclosure documents beyond traditional complexity measures and highlight potential implications for originators, investors and regulators in communicating, understanding and mitigating the risks associated with complex financial instruments.
Keywords: D82; D83; G01; G12; G14; G23; M41; 330; Complexity; Disclosure; Prospectus comprehensibility; Security design; Text analysis